Combination Immunotherapy Use and Withdrawal in Pediatric Inflammatory Bowel Disease—A Review of the Evidence - Meredith, Joseph; Henderson, Paul; Wilson, David C.; Russell, Richard K. (Frontiers in Pediatrics, 2021)
Evidence-based guidelines have been developed outlining the concomitant use of anti-tumour necrosis factor alpha (anti-TNF) agents and immunomodulators including azathioprine (AZA) and methotrexate (MTX) in both adult and paediatric populations. However, there exists a paucity of data guiding evidence-based strategies for their withdrawal in paediatric patients in sustained remission. This narrative review focuses on the available paediatric evidence on this question in the context of what is known from the larger body of evidence available from adult studies. The objective is to provide clarity and practical guidance around who, what, when and how to step-down paediatric patients with inflammatory bowel disease (IBD) from combination immunotherapy. Outcomes following withdrawal of either of the two most commonly used anti-TNF therapies (infliximab [IFX] or adalimumab [ADA]), or immunomodulator therapies, from a combination regimen are examined. Essentially, a judicious approach must be taken to identify a significant minority of patients who would benefit from treatment rationalisation. We conclude that step down to anti-TNF (rather than immunomodulator) monotherapy after at least 6 months of sustained clinical remission is a viable option for a select group of paediatric patients. This group includes those with good indicators of mucosal healing, low or undetectable anti-TNF trough levels, lack of predictors for severe disease, no prior escalation of anti-TNF therapy and short disease duration. Transmural healing and specific human leukocyte antigen (HLA) typing are some of the emerging targets and tools that may help facilitate improved outcomes in this process. We also propose a simplified evidence-based schema that may assist in this decision-making process. Further paediatric clinical studies are required to develop the evidence base for decision making in this area.